2019
DOI: 10.3126/qjmss.v1i2.27448
|View full text |Cite
|
Sign up to set email alerts
|

Graduates Perception on Job Search: A Critical Review

Abstract: Background:The impact of the increased popularity of the internet as a platform to search for jobs may benefit every job seeker as an alternative to generate employment opportunities. Graduates that emphasize on general skills have a higher likelihood of disparitywhile searching for jobs. Objectives:This paper explores graduates’ perceptionson  the knowledge of how to search for jobs from relevant sourcesr. Methods:The theoretical review focuses on job search strategies, job choices and job accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It was found that there are many job portals and recruitment companies inside the Kathmandu valley and maximum people are aware about the services but not utilizing properly because the services being provided are not effective as per the graduates' job search [34]. Due to the limited time period this study covers only primary survey, the improvement of recruitment companies and the more perception of different faculty of students can be analyzed by the secondary data survey as well.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that there are many job portals and recruitment companies inside the Kathmandu valley and maximum people are aware about the services but not utilizing properly because the services being provided are not effective as per the graduates' job search [34]. Due to the limited time period this study covers only primary survey, the improvement of recruitment companies and the more perception of different faculty of students can be analyzed by the secondary data survey as well.…”
Section: Discussionmentioning
confidence: 99%
“…In this era influenced by technology, the conventional hiring and recruitment strategies of the past are no longer adequate to attract the most qualified candidates. Instead, what is needed is a modern and slightly adjusted approach to use technology to empower hiring teams to make more effective and efficient decisions in the recruitment process (Maharjan, 2019). Research by Smith and Jones (2020) highlights the ways social media platforms like LinkedIn, Facebook and Instagram have become integral for connecting job seekers with employers and expanding networking opportunities.…”
Section: The Changing Job Search Landscapementioning
confidence: 99%
“…Nepalese organizations have several prominent e-recruitment sources (Maharjan, 2019), including corporate websites with career pages, job boards, professional networking sites, social networking sites, and human resource (HR) sourcing firms. Banking institutions are known to employ these numerous concurrent modules to connect with potential applicants who could be fit for the open position.…”
Section: Introductionmentioning
confidence: 99%